2022
DOI: 10.1371/journal.pone.0278613
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated calcium entry via ORAI1 regulates doxorubicin-induced apoptosis and prevents cardiotoxicity in cardiac fibroblasts

Abstract: Despite exhibiting cardiotoxicity, doxorubicin (DOX) is widely used for cancer treatments. Cardiac fibroblasts (CFs) are important in the pathogenesis of heart failure. This necessitates the study of the effect of DOX on CFs. The impairment of calcium (Ca2+) homeostasis is a common mechanism of heart failure. Store-operated Ca2+ entry (SOCE) is a receptor-regulated Ca2⁺ entry pathway that maintains calcium balance by sensing reduced calcium stores in the endoplasmic reticulum. ORAI1, a calcium channel protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The human oral squamous cell carcinoma cell lines HSC-3 and OSC-19, which are high metastatic potential lines, were purchased from the Health Science Research Resources Bank (Japan Health Sciences Foundation, Tokyo, Japan) 9 , 46 . The human oral squamous cell carcinoma cell lines SAT and HSC-4 were acquired from the Japanese Collection of Research Bioresources (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human oral squamous cell carcinoma cell lines HSC-3 and OSC-19, which are high metastatic potential lines, were purchased from the Health Science Research Resources Bank (Japan Health Sciences Foundation, Tokyo, Japan) 9 , 46 . The human oral squamous cell carcinoma cell lines SAT and HSC-4 were acquired from the Japanese Collection of Research Bioresources (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analyses were performed as using the following method 9 , 46 . Briefly, cells were lysed and scraped in RIPA buffer (Thermo Scientific, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of cells in the heart, they contain cardiomyocytes, fibroblasts, endothelial cells and smooth muscle cells, of which fibroblasts are the most, accounting for about 75% ( Eghbali, 1992 ; Camelliti et al, 2005 ; Nemoto et al, 2022 ). Their main functions are to produce and maintain the homeostasis of myocardial ECM ( Eghbali, 1992 ; Ottaviano and Yee, 2011 ), as well as produce growth factors (GFs), cytokines and intercellular signaling molecules, affecting cell proliferation, angiogenesis, cardiomyocyte hypertrophy and apoptosis ( Ottaviano and Yee, 2011 ; Mitrokhin et al, 2019 ).…”
Section: Correlation Between Fibroblasts and Cardiac Fibrosismentioning
confidence: 99%
“…Currents through CRAC channels are critically dependent on the correct function of two proteins-Orai1 and STIM1 ( Humer et al, 2022 ). Orai1 is highly expressed in HCFs ( Nemoto et al, 2022 ). A recent study demonstrated that Orai1 expression was upregulated in CFs from failing ventricles, indicating the pivotal role played by Orai1 in HF ( Ross et al, 2017 ).…”
Section: Effects Of Ion Channels On Fibroblast Differentiation or Myo...mentioning
confidence: 99%